Genetic polymorphisms of ARID5B rs7089424 and rs10994982 are associated with B-lineage ALL susceptibility in Chinese pediatric population. Issue 7 (July 2019) - Tao, Ran; Liu, Yu-Jie; Liu, Li-Fang; Li, Wei; Zhao, Yun; Li, Hua-Mei; Yi, Xiao-Lian; Zhao, Zheng-Yan
Abstract : Background: Several ARID5B single nucleotide polymorphisms (SNPs) were confirmed to be significantly associated with the susceptibility of childhood acute lymphoblastic leukemia (ALL) based on Caucasian populations in previous studies. Similar investigations in Asian populations were less. The aim of this study is to explore the relationship between ARID5B SNPs rs7089424, rs10994982, and the risk of ALL in Chinese pediatric population. Methods: A total of 190 pediatric ALL patients and 270 controls were enrolled in this study. PCR amplification combined with mass spectrometry were used to evaluate the genotypes of ARID5B rs7089424 and rs10994982. χ 2 test was used in allele frequencies and genotype distributions of the SNPs for analyzing statistical differences between patients and controls. Results: There were significant differences in the risk allele frequencies of ARID5B rs7089424 and rs10994982 between B-lineage ALL (B-ALL) patients and controls (rs7089424, G allele: p = 0.001; rs10994982, A allele: p = 0.000). The genotype distributions of ARID5B rs7089424 and rs10994982 were also statistically different in B-ALL patients compared with controls (rs7089424, p = 0.004; rs10994982, p = 0.001). Further analyzing the relevance of ARID5B rs7089424 and rs10994982 genotypes to clinical risk classification of ALL showed GG genotype of rs7089424 and AA genotype of rs10994982 were strikingly correlated with the medium-risk and low-risk groups of B-ALL. Finally, GG and GT genotypes of rs7089424 and AA genotype of rs10994982 seemed to be responsible for the hyperdiploid subtype susceptibility of childhood B-ALL. Conclusion: ARID5B rs7089424 and rs10994982 might serve as genetic susceptibility markers for B-ALL in Chinese pediatric population. Moreover, the two ARID5B SNPs are associated with the risk of B-hyperdiploid ALL, which had a better therapeutic response than other ALL subtypes.